2018
DOI: 10.1557/mre.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

Rare earths: A review of the landscape

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 48 publications
0
71
0
11
Order By: Relevance
“…Dichos colores son el resultado de la transición de un electrón entre diferentes orbitales f existentes (transición f-f). Esa diferencia es tan pequeña que basta la energía UV para excitarlos y generar luminiscencia por su efecto, lo que se aprovecha en el billete de 50 euros, al cual se añade una sal de europio que le da su florescencia característica cuando se observa bajo este tipo de luz (Ganguli & Cook, 2018).…”
Section: ¿Por Qué Son Magnéticos Y Luminiscentes Los Elementos De Lasunclassified
“…Dichos colores son el resultado de la transición de un electrón entre diferentes orbitales f existentes (transición f-f). Esa diferencia es tan pequeña que basta la energía UV para excitarlos y generar luminiscencia por su efecto, lo que se aprovecha en el billete de 50 euros, al cual se añade una sal de europio que le da su florescencia característica cuando se observa bajo este tipo de luz (Ganguli & Cook, 2018).…”
Section: ¿Por Qué Son Magnéticos Y Luminiscentes Los Elementos De Lasunclassified
“…Despite the many disadvantages, these wastes contain important amounts of different elements with high commercial value [5,6]. Among these, the rare earth elements (REE) [7] are considered critical raw materials [8], due to the di culty of their separation, acquisition and the uncertainty of their disposition [9]. Recent studies have shown the quantities of REE in LCD screens are economically attractive for recovery, however, the proposed methods have focused mainly on the backlight or light-emitting diodes of the LCD screens [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the REE [7] are considered critical raw materials [8], due to the difficulty of their separation, acquisition and the uncertainty of their disposition [9]. Recent studies have shown the quantities of REE (yttrium, europium, cerium, principally) in LCD screens are economically attractive for recovery it, however, the proposed methods have focused mainly on the backlight or LED´s of the LCD screens [10,11].…”
Section: Introductionmentioning
confidence: 99%